MRV Tools and Resources - CGIAR Research Program on Climate Change, Agriculture and Food Security; Global Research Alliance on Agricultural Greenhouse Gases (CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and Global Research Alliance on Agricultural Greenhouse Gases (GRA), 2018)
Agriculture contributes around 11% of global greenhouse gas emissions. In addition, agricultural emissions are significant at national levels; agriculture contributes an average of 35% of emissions in developing countries and 12% in developed countries. Technical mitigation potential in the agricultural sector is high; there are many low and no-cost options to reduce greenhouse gas emissions, including by improving the efficiency of production. Just over 100 countries include agriculture in their Nationally Determined Contributions (NDCs) under the Paris Agreement and are working to identify and implement mitigation solutions. However, many countries cannot document emission reductions achieved through productivity gains and more efficient farm management because national greenhouse gas inventory reporting systems and supporting data are insufficiently developed. Countries need more robust MRV systems for agricultural greenhouse gas emissions to accurately reflect their national circumstances and transparently demonstrate mitigation. Tools and resources to help countries tailor MRV to their production systems and policy priorities are critical. The Global Research Alliance on Agricultural Greenhouse Gases (GRA) and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) are working together to produce a range of resources to help strengthen MRV systems for agricultural greenhouse gas emissions and mitigation actions.